Rapid urease test provides specific identification of Campylobacter pylori in antral mucosal biopsies. Issue 758 (December 1988) - Szeto, M. L.; Pounder, R. E.; Hamilton-Dutoit, S. J.; Dhillon, A. P.
Abstract : In a prospective study, three antral biopsies were taken from 175 dyspeptic patients during routine endoscopy. One biopsy was inserted immediately into a gel-containing well of a CLOtest slide and two biopsies were sent to histopathology. Using the CLOtest, 84 of the 175 samples (48%) detected urease activity in the gastric biopsy, suggesting infection with Campylobacter pylori. Histopathological examination by two independent observers reported that 93 (52%) of the biopsies contained Campylobacter-like organisms. The CLOtest was found to have a specificity of 1.0 and sensitivity of 0.91, providing a rapid identification of most patients harbouring the organism in their gastric mucus.